Nietzsches ’pile’ - Sentenser og ordsprog - sommeren 1883 - Westergaard, Peter K. (Slagmark - Tidsskrift for idéhistorie, 2018)
This introduction to the Danish translation of the collection of Nietzsche’s aphorisms and proverbs known as “Evil Wisdom” or “Arrows” (from Nietzsche’s Nachlass, notebook Z I 3) explores questions concerning the collection’s origin, context and content. It concludes with a look at some of the philosophical issues that Nietzsche touches on in the collection.